2019
DOI: 10.1080/02791072.2019.1602291
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyltryptamine: Endogenous Role and Therapeutic Potential

Abstract: N, N-dimethyltryptamine (DMT) is an indole alkaloid produced by a number of plants and animals, including humans. Its psychoactive effects were first described in 1956 by Stephen Szára, but have been exploited for centuries by South American indigenous populations throught the use of ayahuasca, an infusion made with a mixture of plants rich in the psychadelic DMT. In the present review, we assess the state of the art regarding a putative role for endogenous DMT and potential future clinical applications. We ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 114 publications
0
12
0
7
Order By: Relevance
“…No clinical studies of DMT use alone in depression treatment were found, as all of the included studies dosed ayahuasca, and it should be remembered that ayahuasca is administered with monoamine oxidase inhibitors, which may have an effect on mood themselves. It should also be remembered that ayahuasca contains other alkaloids, such as harmine or harmaline, and since it is a decoction of the plants themselves, it is difficult to estimate the dose of alkaloids consumed [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…No clinical studies of DMT use alone in depression treatment were found, as all of the included studies dosed ayahuasca, and it should be remembered that ayahuasca is administered with monoamine oxidase inhibitors, which may have an effect on mood themselves. It should also be remembered that ayahuasca contains other alkaloids, such as harmine or harmaline, and since it is a decoction of the plants themselves, it is difficult to estimate the dose of alkaloids consumed [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several additional mechanisms of action have been identified for ayahuasca, positioning it as a potential 'multi-target' drug. These include the activation (by DMT) of both sigma-1 and trace amine-associated receptors (TAAR), suggested to play a key role in addiction behaviours as well as being involved in depression, anxiety and fear extinction (Rodrigues et al, 2019).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Güney Amerika'da, Peru'da DMT içeren "Ayahuasca" meşrubatları içilmektedir. 35 Yine, kargı kamışından yapılan ve Mevlana'nın kullandığı neyde de DMT molekülü bulunmuştur.…”
Section: Dimetiltriptamin (Dmt Molekülü)unclassified
“…Retina periferinde ise her bir ganglion hücresi yaklaşık olarak 200 basil ile bağlantı hâlindedir. Foveada yaklaşık 35.000 kon hücresi bulunur. Her bir kon hücresi, bir ganglion hücresi ile bağlantılı olduğundan foveada görme keskinliği en yüksek seviyededir.…”
unclassified